2020
DOI: 10.1029/2020gl090420
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Geochemical Processes During Hydraulic Fracturing of a Shale Gas Reservoir: A Controlled Field and Laboratory Water‐Rock Interaction Experiment

Abstract: A detailed study on geochemical processes following hydraulic fracturing can provide important information on the origin of solutes and potential improvement of fracturing technology. However, this remains difficult due to the low resolution of flowback water and high salinity of formation water. To fill this knowledge gap, a shale-gas well was drilled and freshwater was used to fracture the shale. In parallel, laboratory water-rock interaction experiments were conducted. The intensive sampling for flowback wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Significant volumes of flowback and produced waters are generated during shale gas extraction (hundreds to tens of thousands of m 3 per well). , Flowback waters return to the surface a few days to a few weeks following hydraulic fracturing and prior to gas production, while produced water is coproduced continuously with the gas once the well is placed into production. , The distinction between flowback and produced waters is neither obvious nor clearly defined, and most studies have reported flowback/produced water data without distinction. , Flowback and produced waters generally consist of highly mineralized Na-(Ca)-Cl waters (thousands to hundreds of thousands ppm total dissolved solids or TDS) with high levels of alkaline earth elements (Ca, Sr, Ba, Ra), alkali elements (Na, K, Li), and halides (Cl, Br) and moderate to low concentrations of dissolved inorganic carbon and sulfate (Figure ). The salinity of flowback/produced water rapidly increases with time after hydraulic stimulation, which is attributed to an increasing proportion of natural formation brines. Saline formation waters are commonly found at depth in sedimentary basins and likely originated as evaporated seawater further modified by water–rock interactions and dilution processes in the shale gas reservoir itself or in adjacent units. …”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%
See 3 more Smart Citations
“…Significant volumes of flowback and produced waters are generated during shale gas extraction (hundreds to tens of thousands of m 3 per well). , Flowback waters return to the surface a few days to a few weeks following hydraulic fracturing and prior to gas production, while produced water is coproduced continuously with the gas once the well is placed into production. , The distinction between flowback and produced waters is neither obvious nor clearly defined, and most studies have reported flowback/produced water data without distinction. , Flowback and produced waters generally consist of highly mineralized Na-(Ca)-Cl waters (thousands to hundreds of thousands ppm total dissolved solids or TDS) with high levels of alkaline earth elements (Ca, Sr, Ba, Ra), alkali elements (Na, K, Li), and halides (Cl, Br) and moderate to low concentrations of dissolved inorganic carbon and sulfate (Figure ). The salinity of flowback/produced water rapidly increases with time after hydraulic stimulation, which is attributed to an increasing proportion of natural formation brines. Saline formation waters are commonly found at depth in sedimentary basins and likely originated as evaporated seawater further modified by water–rock interactions and dilution processes in the shale gas reservoir itself or in adjacent units. …”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%
“…Although there is no WHO guideline for Mn and Sr, concentrations as high as tens of ppm Mn and thousands of ppm of Sr may pose a risk to human health , (Figure ). Elevated concentrations of the alkaline earth elements Sr, Ba, and Ra in flowback/produced waters have been attributed to (1) the limited precipitation of sulfate minerals (e.g., barite, celestite) due to strongly reducing conditions and elevated temperatures in the reservoir and (2) the increased competition for sorption sites on clay minerals and organic matter due to high ionic strength of the fluids. ,, There is still a debate whether Ba and Ra in flowback/produced water are derived from formation brines or are released from black shales during hydraulic fracturing. Elevated B concentrations are thought to result either from carbonate dissolution or desorption from clays. , To our knowledge, no information is currently available regarding the mobilization of F and Mn in flowback/produced waters.…”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been proved that soil disturbance can significantly affect the major ions in the water environment [ 13 ]. Previous studies have analyzed the influence of disturbed soil on the SO 4 content in groundwater through water–rock interactions, such as SO 4 -containing evaporite dissolution and pyrite oxidation [ 16 , 27 ]. However, the detailed causes and mechanisms of water–rock interaction have not been discussed.…”
Section: Introductionmentioning
confidence: 99%